Efektivitas Terapi Komplementer Dalam Meningkatkan Kualitas Hidup Pada Pasien Gagal Jantung: Systematic Review - Paat, Toar Calvin Christo; Erika, Kadek Ayu; Saleh, Arianty (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Introduction: The prevalence of heart failure patients is increasing along with the increase in the global population. Poor quality of life is one of the characteristics of heart failure patients. Complementary therapy might be an alternative to overcome them.. Methods: Â The design of this study is a systematic review using the Preferred reporting items for systematic review and meta analysis (PRISMA) method to compile this paper. The article were collected from online database included PubMed, Science Direct and Google Scholar and publish in 2010 to 2020. Determined articles about intervention articles that discuss the effectiveness of complementary therapies to improve quality of life in heart failure patients.Results: Â Six articles were identified and determined to conduct this systematic review. All studies were conducted using intervention trials of complementary therapy to increase quality of life. Those therapy included Music therapy, a walking exercise program with regulates breathing patterns, benson relaxation, yoga practice, tai chi. These therapy provided by trained nurse. The duration of administration is from 15 minutes to 60 minutes for 3 days to 14 weeks. MLHFQ is the most widely used assessment instrument, the rest are EuroQol, KCCQ and WHOQOL. All studies revealed the significance improvement of quality of life.Conclusion: Â It is conclude that complementary therapy showed strong evidence to improve the quality of life in heart failure patients. in practice, official standard procedures are needed.